Enabling employment for people with disability (PWD): readiness, commitment, and disposition of Malaysian employers - Omar, Muhd Khaizer; Mat Ali, Nor Shailai; Mohd Puad, Mohd Hazwan; Yaakub, Mohamad; Zakaria, Anis (Global Academic Excellence, 2021)
People with disabilities (PWD) struggle with prejudices, narrow-mindedness, and maltreatment. This situation has brought many questions on how the public serves them. Concerning PWDs' employment, the source of income and the wellbeing of this community frequently be neglected and depreciated. The research issues a call to this agenda and suggests action to empower employment among PWD. Descriptive quantitative research was employed to 136 employers from various industries. This article reports three variables: readiness, commitment, and disposition of industrial players on hiring PWD. The results of the study describe that employers are more likely to hire PWD in their organization based on their readiness and commitment, however, the disposition was discouraging. The types of disabilities, industries and ethnicities of the PWD contribute to a major decision when hiring PWD. Employment of PWDs is afflicted by skeptical and dubious perspectives due to their capabilities and capacities to fulfill job responsibilities. With encouragement and empowerment of skilled development programs, PWD is supposed to be allowed to join the workforce, performing a job that suits their impairment. Ongoing support must be advocated among the grassroots of the nations that ultimately flourish the life of PWD.